2000
DOI: 10.1161/01.cir.101.13.1586
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Early Atherogenesis by Losartan in Monkeys With Diet-Induced Hypercholesterolemia

Abstract: This study demonstrates for the first time an antiatherogenic effect of AT(1) receptor blockade in nonhuman primates. Losartan inhibited fatty-streak formation through mechanisms that may include protection of LDL from oxidation and suppression of vascular monocyte activation and recruitment factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
151
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(173 citation statements)
references
References 21 publications
14
151
1
7
Order By: Relevance
“…5,12 Although high BP is an important risk factor in the development of atherosclerosis, the inhibitory mechanism of lipid depo- sition by olmesartan is not related to BP. In this atherosclerotic monkey model, the plasma levels of total and LDL cholesterol in monkeys fed the highcholesterol diet were significantly increased compared with those in the normal-diet monkeys, whereas the levels of HDL cholesterol were significantly reduced (P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,12 Although high BP is an important risk factor in the development of atherosclerosis, the inhibitory mechanism of lipid depo- sition by olmesartan is not related to BP. In this atherosclerotic monkey model, the plasma levels of total and LDL cholesterol in monkeys fed the highcholesterol diet were significantly increased compared with those in the normal-diet monkeys, whereas the levels of HDL cholesterol were significantly reduced (P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…3,5,12 Recent papers have suggested that cytokines, growth factors and adhesion molecules may relate to the development of the atherosclerosis. 3,13 Levels of pro-inflammatory cytokine, M-CSF, are reported to be upregulated with the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of AT 1 blockade has been evaluated in two animal models. 40,41 These studies report an antiatherogenic effect of AT 1 receptor blockade that may be mediated by reduced LDL oxidative susceptibility, reduced MCP-1 levels, and depressed expression of CD11b on circulating monocytes. 40,41 …”
Section: Evidence From Experimental Animal Modelsmentioning
confidence: 99%
“…25 In our original study, we observed that PB monocyte CD11b expression in hypercholesterolemic monkeys was reduced and remained suppressed for at least 2 weeks after discontinuation of losartan treatment. 5 We hypothesized that residual effects related to blockade of AT 1 receptor-mediated myelopoiesis within the BM was responsible for the delay in return to PB monocyte CD11b pretreatment values. Our results in the present study demonstrate that the reduction in CD11b expression was not a direct or immediate effect of losartan on monocytes since PB and BM monocyte CD11b expression was unaffected during the first 3 weeks of treatment with losartan (data not shown).…”
Section: Losartan Normalizes Hsc Function In Hypercholesterolemic Monmentioning
confidence: 99%